2008
DOI: 10.1116/1.2958253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact metals on the piezoelectric properties of aluminum nitride thin films

Abstract: Articles you may be interested inImpact of annealing temperature on the mechanical and electrical properties of sputtered aluminum nitride thin films J. Appl. Phys. 117, 065303 (2015); 10.1063/1.4907208Temperature dependence of the transverse piezoelectric coefficient of thin films and aging effects Stress and piezoelectric properties of aluminum nitride thin films deposited onto metal electrodes by pulsed direct current reactive sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…Sputtered AlN mesa structures have been fabricated using a bottom-up and topdown approach with different metals used for top and bottom contacts. The Pt/Pt contact combination exhibits the highest measured piezoelectric response in mesa structures fabricated using both techniques which is consistent with literature [16]. The residual stress in the metallic thin films was not directly measured in this study; however there is reportedly no correlation between the stress caused by the AlN/electrode mismatch (10.9% for Pt) and the measured d33 value.…”
Section: 6) Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sputtered AlN mesa structures have been fabricated using a bottom-up and topdown approach with different metals used for top and bottom contacts. The Pt/Pt contact combination exhibits the highest measured piezoelectric response in mesa structures fabricated using both techniques which is consistent with literature [16]. The residual stress in the metallic thin films was not directly measured in this study; however there is reportedly no correlation between the stress caused by the AlN/electrode mismatch (10.9% for Pt) and the measured d33 value.…”
Section: 6) Discussionsupporting
confidence: 89%
“…Substrate material has also been reported to increase the piezoelectric response in AlN films due to different nucleation surfaces created by the different materials [15]. Studies have shown that the difference in the piezoelectric effect is closely related to the work function of the substrate and contact metal [16].…”
Section: 3) Introduction To Aluminum Nitridementioning
confidence: 99%
“…40 However, these results are dependent on a complex interplay of deposition parameters, substrate, and seed layers to reduce residual stress. In addition to built-in stress issues, which bias cantilever bending radii, work function effects of contact metal layers 41 were found to alter the piezoelectric response. Also, dielectric losses were found to increase at small AlN thickness 38 which greatly affects the noise behavior in sensors.…”
Section: Theorymentioning
confidence: 99%
“…using Laser Doppler Vibrometer, platinum contacts were deposited using image reversal photolithography. The choice of platinum as top and bottom (p and n) contacts is based on the results reported by Harman et al [35], where it is reported that piezoelectric coefficient d33 is not only function of the crystalline quality of the thin films, but also depends on the work function of the contact metals. have an even, about 1.4 µm thick layer of photoresist.…”
Section: Measurementsmentioning
confidence: 99%